Liquidity and Profitability: Not A "One Size Fits All" Proposition! - Xin Tan; Sorin Tuluca (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- What is the relationship between a company's liquidity and profitability? Motivation- There are two theoretical views in the literature regarding the relationship between liquidity and profitability: one view is that there is a trade-off between the two where too much liquidity decreases profitability, while the other view is that liquidity and profitability are positively correlated. Extant empirical literature, studying larger data sets, does not give a definitive answer to this question as both views have supporting evidence. This research attempts to investigate the reason(s) for such an inconsistent result. Idea- We use the Cash Conversion Cycle (CCC) as measure of liquidity and the Economic Value Added (EVA) as measure of profitability to assess the relationship. Data- The present study uses a large dataset of select S&P 500 sectors and their component companies for a period of twenty-two years extracted from Bloomberg. Tools- We use Python programs to analyze the panel data set with a series of pooled and fixed effects OLS regression models. Findings- The nature and magnitude of the relationship between liquidity and profitability can be positive or negative, statistically significant, or not - the relationship is company specific. Contribution- This study examines the relationship between liquidity and profitability for a wide array of S&P sectors and their component companies. It identifies the relationship for the large S&P 500 set, sector sets and individual companies. The research provides empirical evidence that confirms that the relationship between liquidity and profitability could be positive or negative. The result depends on the data set investigated. For the larger S&P 500data set it might appear that the relationship is negative. However, at sector and company levels the results are mixed.
Keywords: C23; G30; M41; 650; Cash Conversion Cycle; Economic Value Added; Liquidity; Profitability